Gambaran penyebaran COVID-19 di Provinsi Sulawesi Selatan pada bulan Maret-Juli 2020 - Sari, Winda; Siagian, Iyone E. T.; Rombot, Dina V. (UNIVERSITAS SAM RATULANGI, 2020)
Background: Coronavirus is a family virus that causes mild to severe illnesses, such as common cold or cold and serious diseases such as MERS and SARS. Its number in Indonesia is the highest in Southeast Asia. Aims: The purpose of this research is to study the distribution of Covid 19 in South Sulawesi Province. Methods: This study uses a collection of literature conducted by collecting, summarizing, and studying the available literature to get conclusions. The method used to collect data consists of library data that has been selected, searched, presented and analysed. Results: The results of the study showed that prevalence Covid-19 in South Sulawesi Province was one of the highest in Indonesia, with the most affected districts were Makassar, Gowa and Maros. The spread of Covid-19 cases in the province of South Sulawesi from March to July 2020 was 20507 cases. The total number of suspects was 11085 and the positive confirmed patients were 9422 cases, while among confirmed cases as many as 6016 cases were resolved and 314 cases were death.Conclusion: The South Sulawesi Province was one of the most Covid-19 affected provinces in Indonesia up to July 2020.Keywords: Covid-19, Distribution, South Sulawesi Province